The Four Forms of Wealth and Happiness: How Different Forms of Wealth Affect the Subjective Well-being of the Elderly in Europe - Brulé, Gaël (Cham: Springer, 2019)
Wealth is far from being a homogeneous and monolithic concept. Wealth can be positive or negative (e.g. assets versus debts), more or less accessible (e.g. bank accounts versus housing wealth), and more or less time-constrained (e.g. cars versus bonds and mutual funds). These different forms of wealth are likely to influence in different ways the extent to which individuals are satisfied with their life. It is also likely that this influence varies across countries. In this chapter, we characterize four forms of wealth following two axes (positive/negative, mobile/immobile) and link them with the Subjective Well-Being (SWB) of the elderly in Europe. We find that positive mobile wealth is more strongly related to life satisfaction than positive immobile wealth. Negative mobile wealth is also more significantly related to life satisfaction than negative immobile wealth. Possible explanations are discussed using cultural theories.
Keywords: Forms of wealth Seniors SHARE Mobile Immobile life satisfaction